PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING SEBAGAI UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA - P., Silviana Maya (Universitas PGRI Adi Buana Surabaya, 2018)
Classical learning with teacher-centered is regarded as one of the causative factors of low mathematics learning achievement of 11th grade of KR 2 students in SMKN 8 Surabaya. Hence, teachers are required to find and get someway which can reform learning motivation of students. One alternative ways that can be used is by applying Contextual Teaching and Learning approach. This research is a PTK with two cycles, that each cycle has four stages. From the analysis results, it was found that the students' learning outcomes have been classically improved from first to the second cycle. In the first cycle the percentage of students' learning success reached 58.62%. At the same time, in the second cycle, it increased up to 86.20%. Therefore, it can be concluded that the Contextual Teaching and Learning Approach can upgrade the mathematics learning achievement of student, and can be used as an alternative way in learning mathematics. Keywords: Contextual Teaching and Learning Approach, mathematic learning achievement.